Dopamine induces the accumulation of insoluble prion protein and affects autophagic flux - da Luz, Marcio H. M.; Peres, Italo T.; Santos, Tiago G.; Martins, Vilma R.; Icimoto, Marcelo Y.; Lee, Kil S. (Frontiers in Cellular Neuroscience, 2015)
Accumulation of protein aggregates is a histopathological hallmark of several neurodegenerative diseases, but in most cases the aggregation occurs without defined mutations or clinical histories, suggesting that certain endogenous metabolites can promote aggregation of specific proteins. One example that supports this hypothesis is dopamine and its metabolites. Dopamine metabolism generates several oxidative metabolites that induce aggregation of α-synuclein, and represents the main etiology of Parkinson´s diseases. Because dopamine and its metabolites are unstable and can be highly reactive, we investigated whether these molecules can also affect other proteins that are prone to aggregate, such as cellular prion protein (PrPC). In this study, we showed that dopamine treatment of neuronal cells reduced the number of viable cells and increased the production of reactive oxygen species (ROS) as demonstrated in previous studies. Overall PrPC expression level was not altered by dopamine treatment, but its unglycosylated form was consistently reduced at 100 µM of dopamine. At the same concentration, the level of phosphorylated mTOR and 4EBP1 was also reduced. Moreover, dopamine treatment decreased the solubility of PrPC, and increased its accumulation in autophagosomal compartments with concomitant induction of LC3-II and p62/SQSTM1 levels. In vitro oxidation of dopamine promoted formation of high-order oligomers of recombinant prion protein. These results suggest that dopamine metabolites alter the conformation of PrPC, which in turn is sorted to degradation pathway, causing autophagosome overload and attenuation of protein synthesis. Accumulation of PrPC aggregates is an important feature of prion diseases. Thus, this study brings new insight into the dopamine metabolism as a source of endogenous metabolites capable of altering PrPC solubility and its subcellular localization.